Methodology for forecasting precipitation related to El Niño when historical meteorological data are incomplete - María Felicia Jiménez-Lavie; Cecilia Martín-del-Campo; José Luis Lezama-Campos; Edgar Gerardo Mendoza-Baldwin; Rodolfo Silva-Casarín (Revista Facultad de Ingeniería Universidad de Antioquia)
The interactions between the ocean and the atmosphere produce various climatic phenomena, such as the El Niño-Southern Oscillation (ENSO), that influence hydrological systems. This study serves as a basis for water resource management and planning in reservoirs and hydroelectric generation, in both the short and long term. A methodology is proposed to study the potential influence of extreme phases of ENSO on the amount of monthly and seasonal precipitation in areas where the weather stations do not have a complete historical data record. A case study is presented of the seasonal precipitation forecast for the largest water reservoir in Mexico. Data from 18 weather stations in the hydrological sub-region Grijalva-La Concordia, in the state of Chiapas, were examined, the highest on the river course of the rainwater catchment dam of the Grijalva Hydroelectric Complex, the most important complex of its kind in Mexico. From the results it is expected that climate change will bring more frequent El Niño phases. The proposed methodology has been validated, making it an effective tool to evaluate the effects of ENSO on precipitation. The methodology is applicable to other regions, particularly in developing countries where historical information is often incomplete.